Why Health Reforms Fail: Lessons from the 2014 Chilean Attempt to Reform - Pablo Villalobos Dintrans (Taylor & Francis Group, 2019)
In 2014, Chile started a process to reform its private health insurance scheme. A commission was created and released a report with recommendations, but no changes have been introduced yet. This article analyzes that reform process. The analysis included document review and interviews with key stakeholders involved in the process. Results show that although the Commission failed in producing the intended changes, it contributed to opening the debate regarding the Chilean health system, making explicit the different positions on the issue. The analysis shows that the reform did not advance because of the lack of basic consensus on the Commission's role, scope, and main purpose among stakeholders. Previous reforms highlight the relevance of time and information in creating a successful reform process.